Complications after percutaneous transluminal coronary angioplasty and associated factors (Bioscience Journal, 2023)
This study aimed to analyze the incidence of vascular complications and associated factors in patients undergoing elective percutaneous transluminal coronary angioplasty. This study is observational, quantitative, and longitudinal, and followed 50 patients undergoing elective percutaneous transluminal coronary angioplasty. An instrument for the sociodemographic, clinical, procedure, and vascular complications characterization was used for data collection. And descriptive statistics, bivariate analysis, and multiple binomial logistic regression were used for data analysis. The level of statistical significance considered was 95%. It was detected the prevalence of male patients (70%), elderly (54%), and diagnosed with systemic arterial hypertension (72%). As for the percutaneous access route prevailed the radial approach (64%). Age and body mass index were identified as possible risk factors for vascular complications. In the 50 procedures performed, there was a prevalence of hematomas (20%) and bleeding (10%). Among the complications prevailed radial Early Discharge After Transradial Stenting of Coronary (60%), large femoral hematoma (20%), small femoral hematoma (20%), and bleeding (Bleeding Academic Research Consortium 2) (100%). The results concluded an elevated incidence of vascular complications in the first 24 hours after elective percutaneous transluminal coronary angioplasty. This study contributes to research, assistance, and training in health and nursing by identifying post-PTCA vascular complications, minimizing their progression, handling their management, and developing health care safety protocols.